Altered Gene Expression of Cytochrome P450 and ABC Transporter in Human Hepatocellular Carcinoma HepG2 Cells Exposed to Bardoxolone Methyl - Nagai, Katsuhito; Fukuno, Shuhei; Miura, Takeshi; Yasuda-Imanishi, Eri; Konishi, Hiroki (Drug Research, 2023)
Bardoxolone methyl (BX) is expected to be an innovate therapeutic agent for chronic kidney disease (CKD). The aim of the present study was to examine whether the expression of subtypes of cytochrome P450 (CYP) and ABC transporters was altered in human hepatocellular carcinoma HepG2 cells by exposure to BX. The expression of mRNAs for CYP1A2, CYP2E1, P-glycoprotein, multidrug resistance-associated protein 1–3, and breast cancer resistance protein was significantly increased by exposure of HepG2 cells to BX, while the expression of CYP3A4 mRNA was significantly decreased under the same conditions. BX had no significant effect on the expression of mRNAs for CYP2C9 and CYP2C19 in HepG2 cells. In conclusion, this study demonstrated that the gene expression of several CYPs and ABC transporters in HepG2 cells was altered when exposed to BX, suggesting the need to pay careful attention to drug-drug interactions in patients receiving BX for CKD treatment.
Keywords: bardoxolone methyl; drug-drug interaction; cytochrome P450; ABC transporter; HepG2 cell